Using Scattergories Game To Improve Student’s Vocabulary Mastery At The Seventh Grade Of SMP Negeri 2 Tiakur - Unwakoly, Bertha; Lekawael, Rosina F. J.; Meyer, Fredi (Koli Journal : English Language Education, 2022)
The study investigated the effectiveness of the Scattergories game in improving vocabulary mastery among seventh-grade students at SMP Negeri 2 Tiakur through classroom action research. The objectives were to assess the improvement in students' vocabulary and their responses to the game. The data collected through test and questionnaire, and the data analyzed quantitatively. The result showed that initially, students had limited vocabulary knowledge, reflected by low pre-test scores. After implementing the Scattergories game, students showed significant improvement, with post-test scores rising from 65% in the first cycle to 90% in the second cycle. The game helped students understand and memorize new vocabulary easily, and they were enthusiastic and engaged during the learning process. The study concluded that the Scattergories game is an effective method for enhancing vocabulary acquisition and recommended its integration into English teaching practices. Further research is suggested to explore its potential in other areas of English language learning.